Sobre el surgimiento de los derechos indígenas, las tensiones con el Estado-Nación y la consiguiente necesidad de repensar el diseño de nuestras instituciones - Zimerman, Silvina (2011)
This writing deals with the issue of the emergence and recognition of indigenous rights. After a brief synthesis of the iusphilosophical postures that underline the article, the author analyses the indigenous subject at three distinct and fundamental stages: the colonial paradigm, the republican model of Nation state and the contemporary state of affairs- mith XXscentury onwards- It goes on tu affirm status of indigenous rights faithfully mirrors the political and cultural structures inherent to the bourgeois-shaped Nation state. The author concludes bringing forward a redefinition of the notion of equality, an understanding of right as a social construct, and a proposal for an intercultural State, in the light of pluralism and a fairer, more egalitarian society